PEMANFAATAN MEDIA POWER POINT DALAM MENINGKATKAN MINAT DAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SEJARAH DI SMAN 5 CILEGON - Ulul Azmi Rifaldi; Desty Endrawati Subroto; Kurniati Rahmadani (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
The purpose of this research is to find out how the power point media is used at SMAN 5 Cilegon, what the students' motivation and interest in learning are at SMAN 5 Cilegon, how much influence Power Point media has on the motivation and interest in learning. The method used in this research is a descriptive method using a quantitative approach. The location of this research is at SMAN 5 Cilegon, with a population of 30 students, the sampling technique uses a saturated sampling technique, that is, 30 students are sampled from the entire population. The results of the analysis of the coefficients show that the correlation coefficient value shows that the rxy coefficient value is 0.751, so it is stated in the strong category, and the rtable is 0.306. rcount > rtable = 0.751 > 0.306. The results of the t test obtained a value of tcount of 6.026 while ttable of 1.69726 with an error level of 5%, thus tcount > ttable = 6.026> 1.69726, it can be concluded that the correlation coefficient between Powerpoint Media and student interest and learning has a positive and significant effect and from The hypothesis test that was carried out by Ho was rejected and Ha was accepted, and the coefficient of determination (cd) was obtained at 56%. Based on the causal or causal nature of this variable relationship, a simple linear regression equation can be created, namely Y = a + bX, a= 28,941, while the value of b is b = 0.650 X so that there is the influence of media powerpoint interests and student learning motivation at SMAN 5 Cilegon